Experiences and Perceptions About Death Reporting and Notification Among Rural Communities on the Islands of Lake Victoria, Uganda: Qualitative Study - Steven Ndugwa Kabwama; Douglas Bulafu; Rawlance Ndejjo; Rose Nampeera; Christine Kihembo; Chukwuma David Umeokonkwo; Simon Antara; Sheba Nakacubo Gitta; Caroline Kyozira; Allan Muruta; Jean-Edgard Nguessan; Rhoda K Wanyenze (JMIR Public Health and Surveillance)
Abstract BackgroundMortality data are critical for planning and prioritization of public health interventions and are generated through civil registration and vital statistics systems like mortality surveillance systems. However, frameworks for strengthening mortality surveillance systems do not acknowledge the cultural relativism surrounding death and how it influences strategies to improve mortality surveillance systems. ObjectiveThis paper aims to describe the experiences and perceptions about death reporting and notification among rural dwellers on the islands of Lake Victoria in Central Uganda. MethodsThe study was conducted in Buvuma and Kalangala Districts on Lake Victoria using a phenomenological qualitative research design. We conducted 12 in-depth interviews with community members who were purposively identified by village leaders and had experienced the death of a next of kin and reported and notified, and 8 in-depth interviews with those who had experienced the loss of a next of kin but did not notify and report the death. Key informant interviews were also conducted with 2 police officers and 2 cultural leaders. A total of 4 focus group discussions were conducted among village leaders. Interviews were abductively analyzed to generate grand narratives. ResultsThe findings revealed 6 grand narratives of the perceptions and experiences of the process of death reporting and notification among the rural dwellers. These include (1) death reporting and notification are preceded by a tragic event that affects how, when, and if it is conducted; (2) a long and cumbersome process; (3) a process that involves multiple stakeholders with official and unofficial roles and responsibilities; (4) a process with little perceived individual or societal value; (5) a process with several mandatory but unofficial costs; and (6) a process preceded by events with deep cultural undertones. ConclusionsDeath reporting and notification are perceived to be tedious and cumbersome, which discourages community members from conducting them. There is a need to evaluate the process to remove any perceived or actual barriers through strategies such as decentralization of the process to lower levels of political administration. Death reporting and notification are also part of a broader social context that includes cultural beliefs, norms, and traditions. Efforts to strengthen mortality surveillance systems would profit from acknowledging the broader sociocultural issues around death and grieving and the role that cultural and religious institutions can contribute to addressing misconceptions and articulating the benefit of the process to society.